2020
DOI: 10.1111/psyp.13619
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering electrophysiological markers of response inhibition in light of trigger failures in the stop‐signal task

Abstract: This study investigates the neural correlates underpinning response inhibition using a parametric ex‐Gaussian model of stop‐signal task performance, fit with hierarchical Bayesian methods, in a large healthy sample (N = 156). The parametric model accounted for both stop‐signal reaction time (SSRT) and trigger failure (i.e., failures to initiate the inhibition process). The returned SSRT estimate (SSRTEXG3) was attenuated by ≈65 ms compared to traditional nonparametric SSRT estimates (SSRTint). The amplitude an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 75 publications
(139 reference statements)
6
20
1
Order By: Relevance
“…Indeed, EMG and MEP recordings show that the first signs of motor-system inhibition in these measures emerge as early as ∼150ms after the onset of a stop-signal (Jana, Hannah, Muralidharan, & Aron, 2020; Raud & Huster, 2017). In line with this, recent studies have shown that cortical signals that are related to stopping success can also be found in similar time ranges (Huster et al, 2020; Jana et al, 2020; Skippen et al, 2020; Wessel, 2019). Just like the beforementioned EMG and MEP measurements of functional motor inhibition, these cortical signatures often precede both SSRT, as well as the typical onset latency of the fronto-central P3, by several dozens of milliseconds.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Indeed, EMG and MEP recordings show that the first signs of motor-system inhibition in these measures emerge as early as ∼150ms after the onset of a stop-signal (Jana, Hannah, Muralidharan, & Aron, 2020; Raud & Huster, 2017). In line with this, recent studies have shown that cortical signals that are related to stopping success can also be found in similar time ranges (Huster et al, 2020; Jana et al, 2020; Skippen et al, 2020; Wessel, 2019). Just like the beforementioned EMG and MEP measurements of functional motor inhibition, these cortical signatures often precede both SSRT, as well as the typical onset latency of the fronto-central P3, by several dozens of milliseconds.…”
Section: Discussionsupporting
confidence: 66%
“…While this latter association has since been independently replicated (Huster, Messel, Thunberg, & Raud, 2020) the association between the stop-signal P3 and inhibitory processing still remains controversial. One argument is that additional ERPs, including ERPs that predate the P3 and likely reflect attentional processes, also correlate with SSRT (Huster et al, 2020; Skippen et al, 2020). In addition to this debate focusing on the electrophysiology of stopping, the fundamental assumptions underlying the SSRT computation have also recently been called into question themselves, with some authors arguing that SSRT systematically overestimates the latency of the stopping process – specifically because the classic SSRT computation does not take into account trials in which the inhibitory control process is not triggered at all (Matzke, Curley, Gong, & Heathcote, 2019; Patrick Skippen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Second, compared with experiments with humans, monkeys are well trained and well accustomed to the task, typically completing up to 10 times more trials than humans. This may be demonstrated through our observation that monkeys have a much smaller proportion of trigger failures (;5%) compared with what has been previously observed in human (;20%) studies (Skippen et al, 2019(Skippen et al, , 2020. However, although RTs and SSRTs are typically shorter in macaques than humans, the relative relationship between the two is similar between species.…”
Section: Discussionsupporting
confidence: 57%
“…Another potential explanation is that we relied on the stopping speed derived from a button press to measure SSRT. While this is a widely used measure in response inhibition research, it has its drawbacks (e.g., Skippen et al, 2020). Most importantly for our study, the SSRT is only a summary measure for each participant and does not provide single trial information.…”
Section: Discussionmentioning
confidence: 99%